1996
DOI: 10.1063/1.472888
|View full text |Cite
|
Sign up to set email alerts
|

Translational spectroscopy studies of the photodissociation dynamics of O−4

Abstract: An investigation of the photodissociation dynamics of the dimer anion O 4 Ϫ at 523.6, 349.0, and 261.8 nm is reported. Product translational energy and angular distributions have been obtained using photofragment translational spectroscopy in a fast ion beam. At all wavelengths photodissociation ͑O 4 Ϫ ϩh→O 2 ϩO 2 Ϫ ͒ is observed to proceed via a rapid parallel electronic transition, with the photofragment angular distribution strongly peaked along the laser electric vector. The lowest energy photodissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…The resulting value of K 1 dis is calculated to be 0.072 s -1 . A series of experiments (Hanold et al 1995Sherwood et al 1996;Li et al 1997a;Khuseynov et al 2012) designed to clarify the photochemistry of O 4 -have shown that this ion undergoes two photodestruction processes in the wavelength range from 262 to 532 nm: photodissociation (reaction 10 of Table 12) and dissociative photodetachment (reaction 11 of Table 12). As a result of these studies, the O 4 -?hm ?…”
mentioning
confidence: 99%
“…The resulting value of K 1 dis is calculated to be 0.072 s -1 . A series of experiments (Hanold et al 1995Sherwood et al 1996;Li et al 1997a;Khuseynov et al 2012) designed to clarify the photochemistry of O 4 -have shown that this ion undergoes two photodestruction processes in the wavelength range from 262 to 532 nm: photodissociation (reaction 10 of Table 12) and dissociative photodetachment (reaction 11 of Table 12). As a result of these studies, the O 4 -?hm ?…”
mentioning
confidence: 99%
“…The trans O 4 − planar structure that should be more easily formed from O 3 − + O, is only slightly higher in energy (∼37 kJ/mol) [20,21] and is expected to readily interconvert with the rectangular structure [20]. Sherwood et al [22,23] In this mechanism, the change in branching fraction with increasing temperature arises from a decrease in the lifetime of the charge transfer complex with increasing temperature; the charge transfer products separate before the atom/ion transfer can take place. The large fraction of collisions that form charge transfer products regardless of temperature (∼2/3 over our temperature range) may not be involved in this long-lived complex but rather may proceed by a direct or long-range charge transfer mechanism.…”
Section: Resultsmentioning
confidence: 97%
“…The error bars are determined by taking the errors in eKE and ET in quadrature, along with a 20-meV allowance for the precision of the ET measurement. 69 If it is assumed that this rotational energy is shared equally between the two diatom products, a peak value of J 14, corresponding to 40 meV in rotation of each 02, is predicted. The narrow product rotational distribution inferred from the sharp vibrational features implies that dissociation of 04 occurs from a structure with a small exit-channel impact parameter.…”
Section: In This Equation Wj Is the Bound-state Wavefunction For Amentioning
confidence: 99%